MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN FUNGSI GURU DI SMA MUHAMMADIYAH 2 MEDAN - Chairul Azuar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: The problem of this research is Principal Management in improving the function of Teacherin SMA Muhammadiyah 2 Medan. This study aims to find out how the principal formulates policies,regulates work procedures, conducts supervision and Which is a factor supporting and inhibiting thePrincipal in improving the function of teachers in SMA Muhammadiyah 2 Medan. Methodologically,this research is field research (empirical) with qualitative approach. Primary data sources are principals,vice principals, heads and administrative staff, teachers and students. While archival books, activityreports, and management implementation documents are secondary data. In data collection, the methodused is observation, interview, and documentation. In analyzing the data, the researchers used qualitativeanalysis techniques with the steps of data exposure, data reduction, and retraction the conclusions